Precise control of Cu2O nanostructures and LED-assisted photocatalysis. Issue 81 (17th August 2016) - Su, Yang; Nathan, Arokia; Ma, Hanbin; Wang, Hua
Abstract : We describe the synthesis and characterization of a high-efficiency visible light Cu2 O photocatalyst. Abstract : We describe the synthesis and characterization of a high-efficiency visible light Cu2 O photocatalyst. Uniform cubic, octahedral and rhombic dodecahedral Cu2 O nanocrystals with a size of 300–600 nm were synthesized using a simple hydrothermal method. Photocatalytic experiments performed for different water samples (methyl orange solution, toluene solution and industrial wastewater) demonstrate that the rhombic dodecahedral Cu2 O nanocrystals were highly active when driven by low-power white LEDs as a light source. In comparison with other reported photocatalysts, the Cu2 O nanocrystals reported here show a much higher reaction rate and lower electrical energy per order. The reaction rate and photoefficiency were found to be highly correlated with the irradiated photon flux, and the Cu2 O nanocrystals displayed high efficiency in the degradation of aromatic organics. The Cu2 O photocatalyst in this work has the potential to be used for a low-cost and high-efficiency green technology for wastewater treatment.